27 PURIFIED LUNG IMMUNOGLOBULIN G FROM HIV-INFECTED SUBJECTS DEMONSTRATES AN IMPAIRED ABILITY TO OPSONIZE PNEUMOCOCCI. (1st March 2005) - Eagan, R.; Gordon, S. B.; Day, R. B.; Twigg, H. L.
Abstract : Invasive pneumococcal disease is a significant cause of morbidity and mortality in the HIV-infected Malawian population despite high concentrations of anti-pneumococcal antibody concentrations in bronchoalveolar lavage (BAL). Thus we undertook this study to assess the opsonic function of the antibody. 23 HIV-infected and 26 uninfected subjects underwent bronchoscopy with BAL. IgG was purified from BAL on a protein G column. Serotype 1 anti-pneumoccal specific IgG antibody was determined by ELISA. The ability of purified IgG to bind to serotype 1 pneumococci was determined by mixing pneumococcus, purified IgG, and FITC-labelled anti-IgG and analysis by flow cytometry. The ability of FITC-labelled pneumococci coated with purified IgG to bind to monocyte monolayers was determined in a luminometer before and after quenching surface bound FITC with trypan blue. (Table ) Serum and BAL from HIV-infected subjects contained significantly more serotype type 1 specific anti-pneumococcal IgG than normal serum and BAL. Despite this, when equal amounts of purified IgG were added to serotype 1 pneumococci significantly less antibody bound to the organism, both as a percent of pneumococci stained (61 ± 11.8% vs 53 ± 6.6%, p = .001) and as a fluorescent geometric mean indicating intensity of binding. Finally, when serotype 1 specific pneumococci were pretreated with equal amounts of purified BAL IgG, less organisms bound to monocytes after opsonization with HIV IgG compared to normal IgG (60 ± 14% vs 67 ± 14%, p = 0.065). Similar amounts of bound organisms were ingested. These studies suggest that although HIV infection is associated with increased anti-pneumococcal antibody secretion, the antibody demonstrates a significant impairment in its ability to opsonize bacteria. These results may explain the increased susceptibility of HIV-infected subjects to pneumococcal infections. This abstract is funded by NIH RO1 HL62058 (H.L.T.) and the Wellcome Trust (S.B.G.).